A spatial profile of the economy of Boyacá - Arias Gómez, Helmuth Yesid; Antosová, Gabriela (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article aims to make a description of economy in Colombian region of Boyacá, in terms of its spatial implications, identifying a set of municipalities that share some mutual features of productive and geographical sort. Using disposable geo referential information some tools of spatial analysis were applied, in order to find out the spatial features in the agricultural production, and industrial and services unities. In doing so, some theoretical clues are confirmed in the sense that some urban and central places concentrate economic activities, while some local peripheries show low productivity and remain stagnant, as consequence of geographical isolation and poor connectivity.